(3OYGA GdGSe GdCYXe hTQMgs - (3eLghds
(3ChdgG (B:s
(3gPG OYGA GdGSe GdCYXe HMVQI GdbWH GdZhK SjOi GHf eOjf hgh GdMRH GdeTghQ GdeSei GdHQ GdeTghQ s
(3BNQgG (B:s
(3hJcJH ef gPg GdBjI GdTQjaI hgj (B: ( (3hLYdfG ef Hjf CjOjge SOkG hef Ndage SOkG hgPG TQMg Ydi GdJeGe hGdceGd (B) s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdMeQIs
(3HBNQgG NhGU HYV GdBjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs